Student management system / Thevagi Sandrasecra - Thevagi, Sandrasecra (2001)
Overall, it can be said that this project is really important for the administration of students in the school. This system in general requires the retrieval, analysis and reporting of student’s records. Other than that, this system also enables the teachers to tap into the students information system without the hassle of going through student’s manually written records. The manually written record is very hard to locate and it is very time consuming and tedious procedure to be contemplated. Student management system is really a feasible tool since it boast the usage of electronic database. It is a system that will create a faster access to student’s records, speedier retrieval, less redundancy and is able touse high volume application. It again could be said that this system is very easy to navigate and could lessen the burden of the school administrator’s workload.